Exploring the mechanism of proteinuria reduction by hydroxychloroquine in IgA nephropathy using network pharmacology and molecular mocking - Meiqi Lu; Yuxin Wang; Zheng Wan; Yixuan Chen; Mengshu Lin; Xiaoqi Deng; Xiaoxia Su; Qing Gao (Scientific Reports)
Abstract According to the 2021 KDIGO guidelines, hydroxychloroquine (HCQ) had been recommended for the treatment of IgA nephropathy (IgAN). However, the precise mechanisms by which HCQ ameliorated proteinuria in IgAN were not fully understood. This study investigated the potential mechanisms of HCQ in reducing proteinuria in IgAN using network pharmacology and molecular docking approaches. Targets associated with IgAN, proteinuria, and HCQ were identified from databases including DisGeNET, GeneCards, OMIM, and PharmMapper. GO and KEGG analyses were conducted using the DAVID platform. Protein–protein interaction (PPI) networks were constructed using the STRING database, and hub genes were identified using Cytoscape software. The selection of hub genes was corroborated with data from the GEO database and validated through molecular docking. Additionally, miRNAs were predicted using NetworkAnalyst. A total of 48 genes were identified as being associated with the reduction of proteinuria in IgAN. The findings suggested that HCQ’s mechanism of action in mitigating proteinuria in IgAN primarily involved pathways related to inflammation. Furthermore, this mechanism was linked to the regulatory effects of miR-130b-3p on the expression of genes such as MMP2, IGF1, and PPARG. HCQ targeted miR-130b-3p, thereby influencing the TLR/MyD88/NF-κB signaling pathway and modulating the expression of MMP2, IGF1, and PPARG. This action may have been responsible for the observed reduction in proteinuria associated with IgAN.